2018
DOI: 10.1161/circep.117.005959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Spaceflight on Atrial Size, Atrial Electrophysiology, and Risk of Atrial Fibrillation

Abstract: Six months of spaceflight may be sufficient to cause transient changes in left atrial structure and atrial electrophysiology that increase the risk of AF. However, there was no definite evidence of increased supraventricular arrhythmias and no identified episodes of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 38 publications
1
19
1
3
Order By: Relevance
“…Recent data from one study, however, do not support that there is a higher risk for arrhythmia in space—at least not concerning atrial fibrillation . It was in this study reported, though, that the left atrial size measured by magnetic resonance imaging postflight was increased after 6 months of spaceflight, which in itself can predispose to this syndrome .…”
Section: Heart Rate and Rhythmcontrasting
confidence: 70%
See 1 more Smart Citation
“…Recent data from one study, however, do not support that there is a higher risk for arrhythmia in space—at least not concerning atrial fibrillation . It was in this study reported, though, that the left atrial size measured by magnetic resonance imaging postflight was increased after 6 months of spaceflight, which in itself can predispose to this syndrome .…”
Section: Heart Rate and Rhythmcontrasting
confidence: 70%
“…This has, however, been challenged and the data suffer from being collected from a low number of subjects. 93 A specific concern is, whether the increase in cardiac preload, 7,20 stroke volume 33 and left atrial size, 52 which is caused by the weightlessness induced fluid shift per se, in combination with space radiation during long durations of exposures will accelerate occurrences of arteriosclerosis and thus risk of cardiac ischemia and arrhythmia. Therefore, human research through the Gateway project is highly warranted and focus on cardiovascular effects is important.…”
Section: Of 16mentioning
confidence: 99%
“…Dieser Deh-nungsreiz wiederum führt zu einer Freisetzung natriuretischer Peptide, die wiederum eine Relaxation induzieren. Dazu passen Messungen an 13 Astronauten, die unmittelbar nach einem 6-monatigen Weltraumaufenthalt ein durchschnittlich um 12 ml signifikant vergrößertes Volumen des linken Vorhofs aufwiesen [19]. Die Größe des rechten Vorhofs war dabei unverändert, echokardiografische Hinweise auf eine beeinträchtigte Funktion der Vorhöfe fanden sich nicht.…”
Section: Adaptation Des Kardiovaskulären Systemsunclassified
“…Von besonderer Relevanz sind kardiale Probleme während des Aufenthalts in Schwerelosigkeit. Supraventriukuläre und ventrikuläre Extrasystolen (SVES, VES) wurden bei bis zu 30 % aller Astronauten während anstrengender Aktivitäten beobachtet [7]. Auch potenziell lebenslimitierende Arrhythmien, wie Supra-aber auch ventrikuläre Tachykardien wurden in diesem Zusammenhang beobachtet [7]: Ein Bige minus mit einhergehender Synkope aufgrund einer Hypokaliämie, ebenso kurze Episoden einer ventrikulären Tachykardie (VT) wurden bereits beschrieben [8].…”
Section: Kardiale Problemeunclassified
“…Supraventriukuläre und ventrikuläre Extrasystolen (SVES, VES) wurden bei bis zu 30 % aller Astronauten während anstrengender Aktivitäten beobachtet [7]. Auch potenziell lebenslimitierende Arrhythmien, wie Supra-aber auch ventrikuläre Tachykardien wurden in diesem Zusammenhang beobachtet [7]: Ein Bige minus mit einhergehender Synkope aufgrund einer Hypokaliämie, ebenso kurze Episoden einer ventrikulären Tachykardie (VT) wurden bereits beschrieben [8]. Auch wenn diese Ereignisse bisher selten waren, stellen sie eine große Bedrohung mit möglichen lebenslimitierenden Folgen und eine Gefahr für die Mission dar [8].…”
Section: Kardiale Problemeunclassified